2022
DOI: 10.1177/10547738211067880
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Treatment Burden Among Caregivers of Elders With Diabetes and Co-morbid Alzheimer’s Disease and Related Dementias: A Qualitative Study

Abstract: Many older adults with diabetes (DM) have co-occurring Alzheimer’s Disease (AD) and AD-Related Dementias (ADRD). Complex treatment plans may impose treatment burden for caregivers responsible for day-to-day self-management. The purpose of this qualitative study was to describe caregiver perceptions of treatment burden for people with DM-AD/ADRD. Caregivers ( n = 33) of patients with DM-AD/ADRD participated in semi-structured interviews about their caregiver role and perceptions of treatment burden of DM-AD/ADR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Additionally, two studies noted that many caregivers found medication management, for both oral medication and insulin, home glucose monitoring, doctor visits, exercise and diet, challenging and time consuming and had concerns related to medication safety and medication errors 30,32 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, two studies noted that many caregivers found medication management, for both oral medication and insulin, home glucose monitoring, doctor visits, exercise and diet, challenging and time consuming and had concerns related to medication safety and medication errors 30,32 …”
Section: Resultsmentioning
confidence: 99%
“…Informal carers reported feeling very stressed, helpless and frustrated. A study by Dickson et al 32 . illustrated this following a qualitative study of 33 informal carers providing support to people with dementia and diabetes mellitus 32 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations